f-LACUNARY STATISTICAL CONVERGENCE AND STRONG f-LACUNARY SUMMABILITY OF ORDER ? OF DOUBLE SEQUENCES - Sengul, Hacer; Et, Mikail; Altin, Yavuz (Univ Nis, 2020)
The main objective of this article is to introduce the concepts of f -lacunary statistical convergence of order a and strong f -lacunary summability of order alpha of double sequences and give some inclusion relations between these concepts.
Keywords: f -lacunary statistical convergence; strong f-lacunary summability; sequence spaces